AGE CHARACTERISTICS OF PRESCHOOL CHILDREN'S DEVELOPMENT AND PHYSICAL EDUCATION ACTIVITIES (Academia Science Repository, 2023)
The article explores ways to optimize the process of physical education of preschool children based on the targeted use of stratified movement games, as well as the effectiveness of methods of child rearing and ways of mental development of preschool education.